Problem zła w filozofii Józefa Tischnera - Tadeusz Gadacz (Jesuit University Ignatianum in Krakow, 2017)
Themostbasic,primevalaxiologicalexperienceisconnected withdiscoveringthat"thereissomethingthatshouldnotbe".This basic experience of evil provokes man to looking for its signs. Seekingthem,J.Tischnerdifferentiatedthree:theaxiological(referringtovalues),theagatological(referringtotheexperienceof another man) and the structural (referring to participation). Evil is set in the human experience of values, just like good. Andbothofthemexhibitthesamenature:theyarenotobjective but subjective. They happen as a result of human will, which is deep in the middle of dispute between good and evil, evil and good. Human experience is entangled in the essential relation betweengoodandevil,aswellasevilandgood. That is the humandrama.Everymeetingwithanothermanoffersapossibility ofatragedy,inwhich"goodshowsitshelplessnessinthedispute with evil". J.Tischnerputsthequestionaboutthewayevilexistsaside, focusing on its essence, which makes itself felt in human experience. Evil is an "apparition", which appears among people, has some kind of dynamics, which pervade human experience. Whataretheconditionsofthepossibilityofevilemerging?These are:suffering,illusionof pleasure and happiness, and man. Evil which enters between "I" and "You" contains some untruth. However, the limit of its activity is human will. Evil "needs" man in order to show its dynamics, "to happen" and in this meaning evil exhibits the dialogue nature. Thestructuralevildiffersfromthepreviousonessinceitdoes not reveal itself in action, but through participation. Evil which "appears"' and enters among people, acts totally, therefore demonically. It comes out as reality, in which man has a specific share. How can you break free of the demon's control and his tempting to self-annihilation? The way shown by J. Tischner is graceand,followingitstracks,hope.Graceisthegiftofgoodand onlyinitslightdoesitappearmorevisiblehowgoodcanappear in the world of evil.